Persepsi Masyarakat Desa Bagot terhadap Desa Wisata Bagot di Kabupaten Samosir Provinsi Sumatera Utara - Marlina Situmorang; Trisna Putra; Pasaribu Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2023)
The background of this research is the perception of the people of Bagot Village towards Bagot Tourism Village in Samosir Regency which started from the problem that Bagot Village has not been optimized to become a tourism village. And the purpose of this study was to find out how the people of Bagot Village perceive Bagot Tourism Village in Samosir Regency. There are 3 (three) indicators that are seen, namely cognitive, affective, and conative. This type of research is descriptive qualitative data by determining the sample using purposive sampling. The informants of this study were 8 (eight) people. Data collection techniques in research using observation, interviews and documentation. Qualitative data analysis techniques using three ways, namely data reduction, data presentation and conclusion. The research results show that 1). community knowledge of the tourist village, where the community can understand and know the conditions around the tourist village and the problems that occur in the tourist village. 2). From an affective perspective, the people who have been interviewed have responses that show a good attitude towards tourist villages, and 3). From a conative perspective, the community has shown concern for the tourist village, but according to the observations of researchers, the actions taken by the community are only for their own or personal interests.